Chad Public Expenditure Analysis : Fiscal Space for Productive Social Sectors Expenditure - Kitzmuller, Markus; Kassim, Olanrewaju (World Bank, Washington, DC, 2020)
The objective of the Chad Public Expenditure Analysis (PEA) is to examine the technical efficiency and effectiveness of public expenditure, thereby creating fiscal space for more social sector spending. With continued pressures to rationalize expenditure, the government of Chad is interested in finding options to improve the efficiency and effectiveness of public spending, especially in the education and health sectors. In addition, Chad needs to urgently develop structural growth drivers which makes adequate social sector expenditure a priority. Therefore, this PEA explores options to improve (non-oil) revenue mobilization and channel oil revenues towards these social sectors. Finally, a series of policy recommendations is derived from analysis. The PEA is organized around four chapters: chapter one presents short term fiscal developments, long term trends and a medium term macro-fiscal framework. Chapter two serves as an overview and presents detailed analyses of domestic revenues and central government expenditures. Chapter three focuses on the education sector by: (i) analyzing trends and composition of education spending; (ii) examining efficiency in the management and utilization of resources; and (iii) evaluating technical efficiency. Chapter four provides a description of public spending bottlenecks in the health sector while examining resource and expenditure patterns with a focus on technical efficiency and equity of public health spending.